Service charge management in low-cost apartment (Case study : Sri Langkawi II Apartment) / Emelia Aida Abd Aziz - Abd Aziz, Emelia Aida (Faculty of Architecture, Planning and Surveying, 2010)
Condominium, apartment or any strata residential provided with various facilities for residents. Each service provided should be managed and maintained. Because facilities are provided for all residents, so all residents together must pay for the management and maintenance of facilities which is known as service charge. However, every year the management suffered the same problem which is residents do not want to pay the service charge. Based on residents‟ opinion, the facilities provided are not commensurate with the fees charged. Some of them also stated that the facilities are not very well-maintained so they insist on not paying the service charges. As a result of this situation, management was forced to bear the high cost of maintenance every year. The purpose of this dissertation was conducted to examine the factors that cause the residents refused to pay the service charge and find solutions to this problem. In this study, other than feedback from residents regarding with the facilities provided, the opinion of management is taken into account. After the data obtained is analyzed, recommendations will be raised as to overcome this problem.